2010
DOI: 10.15663/wje.v15i1.120
|View full text |Cite
|
Sign up to set email alerts
|

Initial teacher eduction and the a New Zealand curriculum

Abstract: New Zealand teacher educators are faced with the challenge of how to prepare their student teachers to become beginning teachers who are able to base their teaching upon the national curriculum. To meet this challenge, designers of initial teacher education (ITE) programmes need to consider the interface between ITE curriculum and the legislated curriculum for schools. This paper looks at some of the historical influences upon the curriculum in both initial teacher education and schools by examining wider cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The finding that NZ physics teacher educators in their respective colleges decide what content to include in their physics education courses aligns with the assertion by McGee, et al, (2010) that teacher educators in NZ generally continue to have divided opinions over how much subject matter knowledge should be included in teacher education qualifications. That is, there is no national teacher education curriculum, which means that different teacher education providers can prepare teachers differently.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The finding that NZ physics teacher educators in their respective colleges decide what content to include in their physics education courses aligns with the assertion by McGee, et al, (2010) that teacher educators in NZ generally continue to have divided opinions over how much subject matter knowledge should be included in teacher education qualifications. That is, there is no national teacher education curriculum, which means that different teacher education providers can prepare teachers differently.…”
Section: Discussionsupporting
confidence: 62%
“…Findings from the Teaching and Learning International Survey (TALIS) 2013 results indicated that teachers whose initial education included content, pedagogy and practice elements specifically for the subjects they taught, reported feeling better prepared for their work than their colleagues without this kind of training (OECD, 2014). Though the NZ education system has been reported to be attending well to developing understandings of the teaching and learning processes, teacher educators continue to have divided opinions over the subject matter knowledge that should be included in teacher education qualifications (McGee, Cowie, & Cooper, 2010). The recent shift to Masters qualifications for ITE in NZ provides an opportunity to review what subject matter content knowledge is included.…”
Section: The Shortfalls -Figuring Out What Work and What Doesn't Workmentioning
confidence: 99%
“…They imply that initial teacher education is merely the initial phase of teacher preparation. McGee et al (2010) suggest that during the two-year provisionally registered teacher phase, the provision of supervision and mentoring is important. Studies in the Solomon Islands of beginning secondary teachers (Bosamata, 2009;Rodie, 2011) also revealed that beginning teachers are faced with challenges in their first few years of teaching.…”
Section: Professional Development For Beginning Science Teachersmentioning
confidence: 99%
“…7 To guide this process, the 'front end' of the NZC outlines desired philosophical and educational directions through the vision, values and principles statements (McGee, Cowie, & Cooper, 2010). More specifically, the curriculum documents articulate a broad vision of young New Zealanders who are creative, enterprising, actively contributing to a sustainable future, connected and lifelong learners.…”
Section: Outdoor Learning In the Curriculummentioning
confidence: 99%